If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-0.2(z+12)=0.2(9-3z)
We move all terms to the left:
-0.2(z+12)-(0.2(9-3z))=0
We add all the numbers together, and all the variables
-0.2(z+12)-(0.2(-3z+9))=0
We multiply parentheses
-0.2z-(0.2(-3z+9))-2.4=0
We calculate terms in parentheses: -(0.2(-3z+9)), so:We get rid of parentheses
0.2(-3z+9)
We multiply parentheses
-0.6z+1.8
Back to the equation:
-(-0.6z+1.8)
-0.2z+0.6z-1.8-2.4=0
We add all the numbers together, and all the variables
0.4z-4.2=0
We move all terms containing z to the left, all other terms to the right
0.4z=4.2
z=4.2/0.4
z=10+0.2/0.4
| X+e=10 | | -144=-6(5p+4) | | b^2+2b^2-3b^2+b^2=(1+2-3+1)b^2 | | 15x*4x=0 | | 3x²-7x+2=0 | | 34^2=16^2+b | | 12-1.4x=5.4 | | 3(6-6x)=-18 | | 1/4x-1/8x=-1/16 | | -4x-8=4x-16 | | 6x-2=-12+x | | 3+2^(x-5)=19 | | -1(x-1)+4x=-5 | | 3x-10=2x+5=x+20 | | 10^2x=125 | | 2+x/2-10=2/5 | | -7x+2-3x=2 | | 3x-7=-43-x | | 4p^2+25p=-25 | | 3+4m=15 | | 6p^2+7p=-1 | | -5+X+2x=-5 | | 7+x+2x=28 | | -3(y+3)=4y+26 | | -4w-22=3(w-5) | | 3(2+u)-u=4+2(u=1) | | -(2x+4)+7x=136 | | -(2x+4)+7x=1/6 | | 7p+6=5/6p-62 | | 5(x-7)=7x-49 | | 9(6m+7)=54m+63 | | 9=d-3.4 |